2021
DOI: 10.1093/plphys/kiab201
|View full text |Cite
|
Sign up to set email alerts
|

G2/M-checkpoint activation in fasciata1 rescues an aberrant S-phase checkpoint but causes genome instability

Abstract: The WEE1 and ATM AND RAD3-RELATED (ATR) kinases are important regulators of the plant intra-S-phase checkpoint; consequently, WEE1KO and ATRKO roots are hypersensitive to replication-inhibitory drugs. Here, we report on a loss-of function mutant allele of the FASCIATA1 (FAS1) subunit of the chromatin assembly factor 1 (CAF-1) complex that suppresses the phenotype of WEE1- or ATR-deficient Arabidopsis (Arabidopsis thaliana) plants. We demonstrate that lack of FAS1 activity results in the activation of an ATAXIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 60 publications
(60 reference statements)
3
9
0
Order By: Relevance
“… 20 ), different levels of histone variants present in rDNA and/or general redistribution of rDNA genes in the nucleolus 15 , 21 . Our analysis of replication foci clustering in the nucleus did not show significant differences between the wild-type and fas1 or nuc1 mutant plants, in line with a recent report suggesting that the S-phase progression is not delayed in the fas1 background 40 .…”
Section: Discussionsupporting
confidence: 91%
“… 20 ), different levels of histone variants present in rDNA and/or general redistribution of rDNA genes in the nucleolus 15 , 21 . Our analysis of replication foci clustering in the nucleus did not show significant differences between the wild-type and fas1 or nuc1 mutant plants, in line with a recent report suggesting that the S-phase progression is not delayed in the fas1 background 40 .…”
Section: Discussionsupporting
confidence: 91%
“…When plants were treated with 1 mM HU, Col-0 plants showed an extended S-phase duration that is not observed in the wee1-1 plants, consistent with previous reports of the role of WEE1 in arresting the S-phase during the replicative stress response [26,27]. In the polα-2 plants, the HU treatment resulted only in an extended cell cycle duration, whereas in the polα-2 wee1-1 plants both S phase and total cell cycle length increased (Figure 3).…”
Section: The Polα-2 Mutation Causes a Prolongation Of The S-phase And Activation Of The Dna Damage Responsesupporting
confidence: 90%
“…Studies in other eukaryotes have shown that homologous recombination, and in particular the RAD51 protein, is necessary to stabilize stalled replication forks and, in a later stage, restart them [39]. SMR7 is known to respond to several types of DNA damage, both endogenous [27] and exogenous [28], and is induced to a similar extent in the polymerase ε mutant abo4-1 [40].…”
Section: Discussionmentioning
confidence: 99%
“…Our knowledge so far indicates that the loss of telomeric DNA in fas1 and probably also in fas2 plants is not likely to occur via the same mechanism as of rDNA repeats. Telomere erosion in fas1 is mediated by repair processes activated by ATM, which is supported by the recovery of telomere length to WT levels in fas1 / atm plants (Eekhout et al., 2021). Interestingly though, replicative stress caused by the deficiency of RAD3‐related kinase (ATR) kinase also results in increased inter‐individual heterogeneity of telomeres, as was demonstrated in fas1 / atr plants (Eekhout et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from histone metabolism, DNA damage processing factors are the major contributors to the telomere and rDNA instability in fas1 . When double‐strand break (DSB) signalling kinase ATAXIA TELANGIECTASIA MUTATED (ATM) is disrupted in fas1 / atm plants, both telomeres and rDNA are protected against the loss (Eekhout et al., 2021). There are two major ways for the cell to repair DSB: non‐homologous end joining (NHEJ) and homologous recombination (HR).…”
Section: Introductionmentioning
confidence: 99%